Robotic Reconstruction of a Surgically Absent Rectum Using AlloDerm - Reade Otto-Moudry, BA; Elijah Castle, BFA; Gaines Blasdel, BS; Kirtishri Mishra, MD; Jeffery Lin, MD; Rachel Bluebond-Langner, MD; Lee Zhao, MD (Plastic and Reconstructive Surgery, Global Open)
Summary:. This case report and accompanying technique video demonstrate the robotically assisted reconstruction of a surgically absent rectum following prior proctectomy to facilitate receptive anal sex. This novel technique uses AlloDerm to provide the full extent of soft tissue coverage without donor site morbidity and provides a promising avenue for anal canal reconstruction.